Self perceived health and stress in the pregnancy during the COVID-19 pandemic - Liebana-Presa, Cristina; Martínez-Fernández, María Cristina; García-Fernández, Rubén; Martín-Vázquez, Cristian; Fernández-Martínez, Elena; Hidalgo-Lopezosa, Pedro (Frontiers in Psychiatry, 2023)
Introduction: The COVID-19 pandemic has resulted in many maternal and neonatal consequences, especially at the mental level. Pregnant women experience a rise in anxiety symptoms and prenatal stress. Aims: The aim was to describe self-perceived health status, general stress and prenatal stress and to analyze relations and associations with sociodemographic factors. Methods: A quantitative, descriptive and cross-sectional study was conducted using non-probabilistic circumstantial sampling the sample was recruited during the first trimester of pregnancy during the control obstetrical visit. The Google Forms platform was used. A total of 297 women participated in the study. The Prenatal Distress Questionnaire (PDQ), the Perceived Stress Score (PSS) and the General Health Questionnaire (GHQ-28) were used. Results: Primiparas presented higher levels of worry about childbirth and the baby (10.93±4.73) than multiparous women (9.88±3.96). Somatic symptoms were present in 6% of the women. Anxiety-insomnia was scored positively by 18% of the women. In the Spearman correlation analysis, statistically significant values were found between almost all study variables. A positive correlation was observed between self-perceived health and prenatal and general stress levels. Discussion: During the first trimester of gestation, prenatal concerns increase when levels of anxiety, insomnia and depression also increase. There is a clear relationship between prenatal worries, anxiety, insomnia and depression with stress. Good health education with an emphasis on the mental health of pregnant women would be helpful in reducing worries during pregnancy and would improve the pregnant woman's perception of her health and thus her well-being.